Castle of water : a novel - Huckelbridge, Dane (Thomas Dunne Books, 2017)
"Two very different people, one very small island. For Sophie Ducel, her honeymoon in French Polynesia was intended as a celebration of life. The proud owner of a thriving Parisian architecture firm, co-founded with her brilliant new husband, Sophie had much to look forward to--including a visit to the island home of her favorite singer, Jacques Brel. For Barry Bleecker, the same trip was meant to mark a new beginning. Turning away from his dreary existence in Manhattan finance, Barry had set his sights on fine art, seeking creative inspiration on the other side of the world--just like his idol, Paul Gauguin. But when their small plane is downed in the middle of the South Pacific, the sole survivors of the wreck are left with one common goal: to survive. Stranded hundreds of miles from civilization, on an island the size of a large city block, the two castaways must reconcile their differences and learn to draw on one another's strengths if they are to have any hope of making it home. Told in mesmerizing prose, with charm and rhythm entirely its own, Castle of Water is more than just a reimagining of the classic castaway story. It is a stirring reflection on love's restorative potential, as well as a poignant reminder that home--be it a flat in Paris, a New York apartment, or a desolate atoll a world away--is where the heart is"--